Pemenuhan Hak Atas Pangan Dalam Masa Pandemi Covid-19 Berdasarkan ICESCR Serta Implikasi Hukumnya Di Maluku - Christenia Gladysthea Arvita Andries; Josina Augustina Yvonne Wattimena; Lucia Charlota Octovina Tahamata (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: The fulfillment of food rights is contained in the legal instruments of the International Covenant of Economic, Social and Cultural Rights (ICESCR) which has been ratified into Law No. 11 of 2005 concerning the Ratification of the Covenant on Economic, Social and Cultural Rights.Purposes of the Research: To review and analyze the fulfillment of food rights during the covid-19 pandemic based on ICESCR and its legal implications in Maluku.Methods of the Research: The research method used is normative juridical. The problem approach used is conceptual approach, and statutory approach, the source of legal materials used is the source of primary and secondary legal materials. Collection techniques through literature studies and then analyzed through a description method using qualitative methods.Results of the Research: The legal implications of fulfilling food rights in Maluku during the covid-19 pandemic have not been properly met due to the policy of restricting social movements that resulted in the traffic of sea transportation between islands in Maluku is hampered so that people have difficulty addressing basic food needs. National food sufficiency does not guarantee that all communities get the food they need. Found five aspects that are quite influential to the problem of food availability. among others, the increasing population, declining food production and productivity, the occurrence of climate change, conservation of agricultural land and still high proportion of lost yields in the production process, handling of crops and processing. Then, food distribution problems include, distribution systems that have not been well organized, land and inter-island distribution infrastructure that is not adequate, while for food consumption problems that are not diverse and nutritious enough balanced.  And when a violations of covenant obligations in the fulfillment of food for the community then it can be prosecuted as stipulated in the principles limbur.